A family case report of Neurofibromatosis - Wolder, Daniel; Swat, Adrian (Journal of Education, Health and Sport, 2022)
Neurofibromatosis is a genetic disease inherited in an autosomal, dominant manner. The course of von Recklinghausen’s disease varies from patient to patient. Most cases are mild and uncomplicated. The diagnosis of NF1 is based on the criteria of the National Institutes of Health (NIH). Type 2 neurofibromatosis is inherited, in most cases autosomal dominantly. The abnormal allele can be inherited from either parent, with the risk of passing the gene on to the offspring from the parent, being 50%. This article describes the familial form of neurofibromatosis. In the case in question, all three sisters were found to be mutated in the NF1 gene by genetic testing. In the same family, the clinical manifestation of the disease may be different for sisters and children. Due to compliance with medical recommendations, the disease does not significantly affect the quality of life of the families affected.